Seasonal variations in objectively assessed physical activity among people with COPD in two Nordic countries and Australia: a cross-sectional study - Hoaas,Hanne; Zanaboni,Paolo; Hjalmarsen,Audhild; Morseth,Bente; Dinesen,Birthe; Burge,Angela T; Cox,Narelle S; Holland,Anne E (International Journal of Chronic Obstructive Pulmonary Disease, 2019)
Hanne Hoaas,1,2 Paolo Zanaboni,1 Audhild Hjalmarsen,3,4 Bente Morseth,5 Birthe Dinesen,6 Angela T Burge,7–9 Narelle S Cox,7,9 Anne E Holland7–91Norwegian Centre for E-health Research, University Hospital of North Norway, Tromsø, Norway; 2Faculty of Health Sciences, UiT The Arctic University of Norway, Tromsø, Norway; 3Department of Clinical Medicine, UiT The Arctic University of Norway, Tromsø, Norway; 4Department of Pulmonary Medicine, University Hospital of North Norway, Tromsø, Norway; 5School of Sport Sciences, UiT The Arctic University of Norway, Tromsø, Norway; 6Laboratory of Welfare Technologies – Telehealth & Telerehabilitation, SMI, Department of Health Science and Technology, Aalborg University, Aalborg, Denmark; 7Discipline of Physiotherapy, La Trobe University, Melbourne, Australia; 8Department of Physiotherapy, Alfred Health, Melbourne, Australia; 9Institute for Breathing and Sleep, Melbourne, AustraliaPurpose: Seasons and weather conditions might influence participation in physical activity and contribute to differences between countries. This study aimed at investigating whether there were differences in physical activity levels between Norwegian, Danish and Australian people with chronic obstructive pulmonary disease (COPD), and establishing if any variations in physical activity were attributable to seasons.Patients and methods: A cross-sectional study where study subjects were people with COPD who participated in two separate clinical trials: the iTrain study (Norway, Denmark, and Australia) and the HomeBase study (Australia). Physical activity was objectively assessed with an activity monitor; variables were total energy expenditure, number of daily steps, awake sedentary time, light, and moderate-to-vigorous intensity physical activity. Differences in physical activity between countries and seasons were compared, with adjustment for disease severity.Results: In total, 168 participants were included from Norway (N=38), Denmark (N=36) and Australia (N=94). After controlling for disease ...